Aspects of the Greek campaign, April 1941 : a thesis submitted in partial fulfilment of the requirements for the degree of Master of Arts in Defence Studies, Massey University - Ormond, W. L. (Massey University, 2009)
This thesis examines the circumstances by which the British became involved in Greece in 1941. It shows that the British government was influenced by the Prime Minister, Winston Churchill, and more importantly by his emissary to the Middle East, the Foreign Secretary Anthony Eden. The government had no clear idea of what they hoped to achieve beyond the vain hopes of building a coalition in the Balkans against Axis expansion in that region. This they failed to achieve, and the poorly equipped and under-manned expedition they despatched had little chance of military success against a better equipped and organised enemy. An analysis of the equipment and numbers of the Allied and Axis forces reveals the handicap suffered by the inadequately supplied Allied troops in Greece had little chance of holding the well-prepared German forces. The question of whether the British government deliberately misled the New Zealand and Australian governments in their quest to use Dominion troops in Greece is considered and a judgement made. The performance of one unit of the New Zealand Expeditionary Force, 21 Battalion, is examined and is found to be wanting, mainly because of poor leadership by its commanding officer. An examination of this officer's personality and defeatist attitude reveals how his command affected the battalion's performance. This is contrasted with the courage and hardiness shown by his men when they were no longer under his influence during their escape after the action at Pinios Gorge. Finally, the reporting of the campaign in the New Zealand official histories shows that these avoided criticism of any deficiencies in the New Zealanders' performance, and a more recent work which relied heavily on these histories for its information is similarly flawed in the picture it presents.
Keywords: Greece, 1941; Second World War; World War Two; New Zealand Expeditionary Force, 21 Battalion